THE INFLUENCE OF SUPPLIER RELATIONSHIP MANAGEMENT TOWARD BUSINESS PERFOMANCE OF SMES IN MANADO - Tundunaung, Anatya G. C.; Tumbuan, Willem J. F. A.; Tasik, Hizkia H. D. (FEB Universitas Sam Ratulangi Manado, 2021)
Supplier Relationship Management offers lots of advantages. Implementing this system will eventually lead to different types of challenges, such as finding the right vendors or suppliers with good capabilities, having executive sponsorship, and creating business cases. Implementing this type of management also needs to be followed by requirements that can make or break the system's effectiveness. The purpose of this study is to find out whether the components of Supplier Relationship Management such as information sharing, joint activity, and trust-based relationship affect the business performance of Small and Medium Enterprises in Manado. This study uses a quantitative method and ordinal regression analysis as a tool to analyze the data. This study's findings show that information sharing, joint activity, and trust-based relationships significantly affect business performance. From the results, SME owners can make several improvements, such as focusing on aspects that influence business performance, implementing electronic data interchange, and maintaining trust-based relationships towards suppliers.Â Â Keywords: supplier relationship management, information sharing, joint activity, trust-based relationship, business performanceÂ